The shoemaker's wife : a novel - Trigiani, Adriana (New York : Harper, 2012)
Two star-crossed lovers--Enza and Ciro--meet and separate, until, finally, the power of their love changes both of their lives forever. Set during the years preceding and during World War I.
Includes a 12 page section at the end of the book entitled PS: Insights, interviews and more...
Keywords: Italian Americans -- Fiction; Shoemakers -- Fiction; Women dressmakers -- Fiction; Separation (Psychology) -- Fiction; Life change events -- Fiction; Immigrants -- Fiction; Man-woman relationships -- Fiction; New York (N.Y.) -- Fiction; Love stories; Historical fiction